1965
DOI: 10.1113/jphysiol.1965.sp007786
|View full text |Cite
|
Sign up to set email alerts
|

Dark adaptation and increment threshold in a rod monochromat.

Abstract: The well-known fall in sensitivity of the eye when exposed to light and the subsequent rise in the dark has long been attributed to the bleaching and subsequent regeneration of rhodopsin and of cone visual pigments. This conjecture, held for thirty years without evidence, was shown to be on the right lines when Dowling (1960) demonstrated in rats that, after full bleaching, there was at each stage of regeneration a linear relation between the amount of rhodopsin in the retina and the log e.r.g. threshold at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
1

Year Published

1966
1966
2006
2006

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 29 publications
6
60
1
1
Order By: Relevance
“…An early set of experiments (Rushton & Westheimer, 1962;Rushton, 1965b) involving threshold measurements upon bleaching fields which were either uniform or patterned (gratings or spotted) seemed to indicate that bleaching effects spread uniformly in 'adaptation pools' (Rushton, 1965 a) of at least 30 minutes of arc. Within such pools, differences in adapting luminance seemed to cause no local variations in sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…An early set of experiments (Rushton & Westheimer, 1962;Rushton, 1965b) involving threshold measurements upon bleaching fields which were either uniform or patterned (gratings or spotted) seemed to indicate that bleaching effects spread uniformly in 'adaptation pools' (Rushton, 1965 a) of at least 30 minutes of arc. Within such pools, differences in adapting luminance seemed to cause no local variations in sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The equipment was the same as that recently described (Blakemore & Rushton 1965a). The subject was fixed in position with dental impression and brow rest and the lights entered his eye by Maxwellian view.…”
Section: Methodsmentioning
confidence: 99%
“…Blakemore & Rushton (1965) measured increment threshold in a rod-monochromat with 1 s duration, achromatic flashes of large and small target diameter. They found that the curve measured with a small (5 min of arc) diameter flash rose with a slope of 0-59, whereas that measured with a large (6 deg) diameter flash rose with a slope of 0-87.…”
Section: T Sharpe and Othersmentioning
confidence: 99%